KHORAZM IN THE PERIOD OF KHORAZMSHAH ALI IBN MAMUN (TAMADDUN NURI JURNALI, 2024)
Ali ibn Mamun, who is considered one of the most prominent representatives of the Mamunids dynasty, during his career, entered into relations with the Arab caliph along with the peoples located in the regions of South Siberia. In this article, the history of Ali ibn Mamun's relations with the large states of Karakhanids and Ghaznavids in Central Asia, as well as the history of receiving the title from the Arab caliph, is analyzed using numismatic sources.